Analisis Realisasi Perencanaan Pemberdayaan Masyarakat dalam Pelaksanaan Program Pemerintah Desa Nazalou Lolowua Kecamatan Gunungsitoli Alo’oa - Zega, Darman Syah; Waruwu, Eliyunus; Telaumbanua, Eliagus; Waruwu, Meiman Hidayat (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: In this research, the researcher will analyze the realization of community empowerment in village programs in the government of Nazalou Lolowua Village, Alo'oa District, Gunungsitoli. During the research observation, the researcher found dissatisfaction among the villagers regarding the lack of availability and quality of sewing course training organized by the village government. Method: The objectives of this research are to determine the analysis of the realization of community empowerment planning in the implementation of Village Government programs and to identify efforts to achieve the realization of community empowerment planning on the programs of Nazalou Lolowua Village Government, Alo'oa District, Gunungsitoli. This research employs qualitative methods and data collection techniques involving observation, documentation, and interviews. Results: The findings of this research indicate that the Nazalou Lolowua Village Government, in the development of the economic programs for the Nazalou Lolowua Village community, specifically in sewing and computer courses, faces limitations in terms of the quantity of sewing machines and computers procured, limited training time, and limited community participation. Conclusion: As a result, the planning fulfillment in community economic development is not comprehensively accommodated and cannot be developed by the community in their daily lives. The Nazalou Lolowua Village Government needs to make efforts to meet the needs of the community by absorbing aspirations to understand the actual conditions required by the community.